2005
DOI: 10.1099/vir.0.80546-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of avian infectious bronchitis coronavirus from domestic peafowl (Pavo cristatus) and teal (Anas)

Abstract: Coronavirus-like viruses, designated peafowl/China/LKQ3/2003 (pf/CH/LKQ3/03) and teal/China/LDT3/2003 (tl/CH/LDT3/03), were isolated from a peafowl and a teal during virological surveillance in Guangdong province, China. Partial genomic sequence analysis showed that these isolates had the S-3-M-5-N gene order that is typical of avian coronaviruses. The spike, membrane and nucleocapsid protein genes of pf/CH/LKQ3/03 had >99 % identity to those of the avian infectious bronchitis coronavirus H120 vaccine strain (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
132
1
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(149 citation statements)
references
References 43 publications
7
132
1
6
Order By: Relevance
“…This virus, identified as QX, was associated predominantly with various forms of renal pathology. Following this first report, other investigators have described the circulation of similar strains in China (Liu et al, 2005). Cuiping et al (2007) confirmed data presented by Liu et al (2005), reporting the isolation of nephropathogenic strains from vaccinated and unvaccinated chicken flocks between 2003 and 2005. A retrospective phylogenetic analysis on IBV strains isolated in Russia between 1998 and 2002 showed the isolation from a broiler farm of genetically related QX virus in the Far East of Russia in 2001 (near the border with China) (Bochkov et al, 2006).…”
Section: Introductionsupporting
confidence: 68%
“…This virus, identified as QX, was associated predominantly with various forms of renal pathology. Following this first report, other investigators have described the circulation of similar strains in China (Liu et al, 2005). Cuiping et al (2007) confirmed data presented by Liu et al (2005), reporting the isolation of nephropathogenic strains from vaccinated and unvaccinated chicken flocks between 2003 and 2005. A retrospective phylogenetic analysis on IBV strains isolated in Russia between 1998 and 2002 showed the isolation from a broiler farm of genetically related QX virus in the Far East of Russia in 2001 (near the border with China) (Bochkov et al, 2006).…”
Section: Introductionsupporting
confidence: 68%
“…d The genome organisation, gene sequences and biological properties of these isolates were such that it is possible that they were actually IBVs; domestic fowl were kept nearby. The peafowl isolate of Liu et al [66] had > 99% genome sequence identity with the IB vaccine strain H120. The teal duck isolate caused disease when experimentally inoculated into chickens [66].…”
Section: Pathogenesis Of Ibvmentioning
confidence: 99%
“…the peafowl but also in non-galliform birds e.g. the teal, which is a duck [66]. Indeed, some of the long-known mammalian coronaviruses have a wider host range than their name would suggest, and SARS-CoV is a case in point.…”
Section: Introductionmentioning
confidence: 99%
“…The isolate in China from a teal */also kept domestically, near chickens */had a spike protein that had Â/90% identity with some known IBV strains, including a nephropathogenic one (Liu et al ., 2005; databank accession number for the whole genome sequence, AY702975). When this isolate was inoculated into chickens, it caused disease, including kidney involvement.…”
Section: Coronaviruses In Non-galliform Birdsmentioning
confidence: 99%
“…The proteins of the peafowl virus had !/99% identity with the widely used IBV H120 vaccine (Liu et al ., 2005: databank accession number for the whole genome sequence, AY702085). This extremely high degree of identity makes it almost certain that it was the vaccine strain that had been recovered from the peafowl, which had chickens in the neighbourhood.…”
Section: Coronaviruses In Other Galliform Birdsmentioning
confidence: 99%